Using Google Form as an Evaluation Tool for Physics Learning in Phase F - Hikmawati, Hikmawati; Rokhmat, Joni; Dewi, Alfiana Chandra; Firdaus, Fahmi; Farrizqi, Muhammad Nur; Nisaa, Muthiatun; Hadi, Yayan Sofyan (Balai Publikasi Indonesia, 2022)
This study aims to analyze the use of Google Forms as an evaluation tool for learning physics in Phase F at SMAN 1 Masbagik. The analysis was divided into two, namely students' mastery of physics concepts on Fluid Statics in terms of the question categories and students' responses to the use of google forms. This study used 18 respondents from Phase F at SMAN 1 Masbagik, East Lombok Regency, West Nusa Tenggara. This research was conducted in an odd semester of the 2022 school year. The link to the evaluation questions given to respondents contained 15 questions with 5 answer options, namely A, B, C, D, and E. Links to student response questionnaires for using the evaluation tool in the form of a Google form containing 10 attitude statements, with an assessment using a scale of 4. The results showed that students who answered correctly in the easy category were 72.2%, the medium category was 50.0%, and the difficult category was 33.3%. Students who expressed interest in the Google form as an evaluation tool amounted to 35.7%, and students who stated that they were very satisfied with the Google form as an evaluation tool amounted to 42.9%. Thus, teachers need efforts to train students in working on questions that fall into the difficult category or Higher Order Thinking Skills (HOTS). The Google form can be an alternative evaluation tool in physics learning, especially during the COVID-19 pandemic which limited direct learning interactions in class